A fast forward algorithm for real-time geosteering of azimuthal gamma-ray logging. (May 2017) - Qin, Zhen; Pan, Heping; Wang, Zhonghao; Wang, Bintao; Huang, Ke; Liu, Shaohua; Li, Gang; Amara Konaté, Ahmed; Fang, Sinan
Abstract: Geosteering is an effective method to increase the reservoir drilling rate in horizontal wells. Based on the features of an azimuthal gamma-ray logging tool and strata spatial location, a fast forward calculation method of azimuthal gamma-ray logging is deduced by using the natural gamma ray distribution equation in formation. The response characteristics of azimuthal gamma-ray logging while drilling in the layered formation models with different thickness and position are simulated and summarized by using the method. The result indicates that the method calculates quickly, and when the tool nears a boundary, the method can be used to identify the boundary and determine the distance from the logging tool to the boundary in time. Additionally, the formation parameters of the algorithm in the field can be determined after a simple method is proposed based on the information of an offset well. Therefore, the forward method can be used for geosteering in the field. A field example validates that the forward method can be used to determine the distance from the azimuthal gamma-ray logging tool to the boundary for geosteering in real-time. Highlights: A fast forward algorithm is proposed to geosteer using azimuthal gamma-ray logging. A simple method is proposed to determine the formation parameters of the algorithm. Distance from logging tool to boundary can be obtained using the forward method.